Deliberasi dalam Perencanaan Pembangunan Infrastuktur Nagari Kunangan Parit Rantang, Kecamatan Kamang Baru pada Masa Covid-19 - Lingga Elissa (LPPM Universitas Abdurrab, 2022)
This article discusses the deliberative process to make the result in the form of an agreement that is used as a policy or the basis for a management plan of a government entity. The focus of the research includes four things, first, Deliberation Process in Development Planning of Nagari Kunangan Parit Rantang, second, Groups Involved in Musrenbang Nagari Kunangan Parit Rantang, third, Indicators of Successful Implementation of Musrenbang, and fourth, Differences in Implementation of Musrenbang in Nagari Kunangan Parit Rantang during the period Before the Pandemic and During the Pandemic. The purpose of this study was to find out how the community participated in the discussion on infrastructure development in Nagari Kunangan Parit Rantang, Kecamatan Kamang Baru during the COVID-19 pandemic. The COVID-19 pandemic has affected the scale of infrastructure development in Nagari Kunangan Parit Rantang, Kecamatan Kamang Baru. This research method uses a qualitative method which was developed through a phenomenon and is supported by the opinions of experts using previously obtained data. The conclusion obtained in this study is the understanding of deliberative democracy in infrastructure development in Nagari Kunangan Parit Rantang, Kecamatan Kamang Baru.